Utilization of natural polysaccharide from Tamarindus indica L. seeds for the effective reduction of pollutants in cheese processed wastewater. (October 2022) - Sofiavizhimalar, A.; Sunithajasmine, B.; Rajalakshmi, B. Sowmiya; Thamaraiselvi, C.; SumathiJones, C.; Pandey, Sadanand; Alfarhan, Ahmed; Muthusamy, Karnan; Chang, Soon woong; Ravindran, Balasubramani
Abstract: The present study was targeted to treat the cheese factory processed wastewater by using natural coagulants. The results were compared with the CPCB wastewater discharge limit and most of the parameters were exceeded the standard limit. In the present investigation, the processed wastewater was subjected to treatment with Tamarindus indica L. plant seed as a coagulating agent. The processed wastewater was treated with Tamarindus indica L. seed powder which is rich in polysaccharides. The proximate analysis confirmed the presence of higher content of carbohydrates, protein, and fiber. Different dosages were used for the treatment. Accurately 0.4 gm was recorded as optimum dosage for the effective removal of pollutants includes 71% of TDS and 75% of COD from the cheese processed wastewater. The GC-MS analysis of raw and treated cheese processed wastewater was carried out and the results showed the degradation of toxic compounds and reduction of pollutants from the processed wastewater. FTIR analysis of T.indica L . seed powder disclosed various chemical group presence and proved higher efficiency in seed treatment. Graphical abstract: Image 1 Highlights: T. i ndica L. seed powder which is rich in polysaccharides, protein and fiber. Polysaccharides effectively removed 75% of COD from cheese processed wastewater. The optimum dosage of 0.4 g seed was recorded as effective removal of pollutants. The highest of 120 min duration was taken for maximum removal percentage.